Method for manufacturing an electric cell, electric cell, battery, vehicle and electric device
Patent Information
- Application Number
- CN202610243711.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请所要解决的技术问题是提供一种电芯的制备方法、电芯、电池、车辆和用电装置,以解决相关技术中CEI膜的成膜方式导致电芯的循环使用寿命下降的问题
本申请实施例所提供的电芯的制备方法,在电芯装配之前,在正极极片上制备正极电解质界面膜,可以在不消耗电芯中电解液的活性组分的情况下,在正极极片上形成正极电解质界面膜,本申请实施例通过将正极电解质界面膜的形成过程置于电芯装配之前,在对电芯进行首次充放电之前,正极极片上的正极电解质界面膜已经形成,在对电芯进行首次充放电的过程中,在正极电解质界面膜的阻挡作用下,正极极片中的正极活性材料不再与电芯中封装的电解液直接接触,避免了正极电解质界面膜的成膜过程对电解液中活性成分的消耗,有利于提高电芯内部封装的有效电解液的存量,减缓电芯在充放电循环过程中活性离子传输的浓度极化效应,降低活性离子的不可逆损耗,有利于提高电芯的电化学性能,延长电芯的循环使用寿命。
Smart Images

Figure CN123018160A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a method for preparing a battery cell, a battery cell, a battery, a vehicle, and an electrical device. Background Technology
[0002] The cathode electrolyte interface (CEI) is an interfacial film formed by the oxidation reaction between the positive electrode active material and the electrolyte in the positive electrode sheet. During charge-discharge cycles, the CEI film can suppress the side reaction process between the positive electrode active material and the electrolyte, and improve the interfacial stability between the positive electrode active material and the electrolyte.
[0003] In related technologies, a CEI film is typically formed at the interface between the positive electrode active material and the electrolyte during the first charge-discharge phase of the battery cell after electrolyte injection and encapsulation. However, the formation of the CEI film consumes the active components in the electrolyte, resulting in a significant reduction in the effective electrolyte content inside the battery cell. This reduced electrolyte content exacerbates the concentration polarization effect of active ion transport during charge-discharge cycles, accelerates the irreversible loss of active ions, and ultimately leads to a decrease in the cycle life of the battery cell. Summary of the Invention
[0004] The technical problem to be solved by this application is to provide a method for preparing a battery cell, a battery cell, a battery, a vehicle, and an electrical device, so as to solve the problem that the CEI film formation method in related technologies leads to a decrease in the cycle life of the battery cell.
[0005] To solve the above-mentioned technical problems, this application provides the following technical solution: This application discloses a method for preparing a battery cell, the method comprising: Before cell assembly, a positive electrode electrolyte interface film is prepared on the positive electrode sheet.
[0006] Furthermore, the preparation of a positive electrode electrolyte interface film on the positive electrode sheet before cell assembly includes: Before cell assembly, the positive active material in the positive electrode sheet is immersed in a pretreatment solution to prepare a wetted electrode sheet. The pretreatment solution includes film-forming components of the positive electrode electrolyte interface film. The wetted electrode is subjected to microwave treatment to prepare a positive electrode electrolyte interface film on the surface of the positive electrode active material of the positive electrode.
[0007] Furthermore, the film-forming component includes at least one of vinylene carbonate, fluoroethylene carbonate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, ethylene sulfate, and lithium bis(oxalato)borate.
[0008] Furthermore, in the pretreatment solution, the concentration of the film-forming component is 0.1 wt% to 10 wt%.
[0009] Furthermore, in the pretreatment solution, the concentration of the film-forming component is 1wt%~5wt%.
[0010] Further, the step of immersing the positive active material in the positive electrode sheet in a pretreatment solution to prepare the wetted electrode sheet includes: The positive electrode active material in the positive electrode sheet is immersed in the pretreatment solution; When the positive electrode active material is immersed in the pretreatment solution for a first time, the positive electrode sheet wetted with the pretreatment solution is removed from the pretreatment solution and suspended in the air until the suspension time reaches a second time or no liquid drips from the surface of the positive electrode sheet within a third time, thus obtaining the wetted electrode sheet.
[0011] Furthermore, the first duration is 5 min to 30 min; and / or, the second duration is greater than or equal to 30 min; and / or, the third duration is 1 min to 5 min.
[0012] Furthermore, the power of microwave treatment of the impregnated electrode is 100W~1000W, and the duration of microwave treatment of the impregnated electrode is 5min~20min.
[0013] Further, the step of microwave treating the wetted electrode to prepare a positive electrode electrolyte interface film on the surface of the positive electrode active material of the positive electrode includes: The wetted electrode sheet is subjected to microwave treatment to obtain a microwave electrode sheet; The positive electrode active material in the microwave electrode sheet is immersed in the target solvent; When the positive electrode active material is immersed in the target solvent for a period of four time, the microwave electrode sheet immersed in the target solvent is removed from the target solvent and suspended in the air until the suspension time reaches a period of five time or no liquid drips from the surface of the microwave electrode sheet within a period of six time, thus obtaining a cleaned electrode sheet. The cleaned electrode is dried to obtain a positive electrode electrolyte interface film formed on the surface of the positive electrode active material of the positive electrode.
[0014] Furthermore, the fourth duration is 5 min to 30 min; and / or, the fifth duration is greater than or equal to 30 min; and / or, the sixth duration is 1 min to 5 min.
[0015] Furthermore, the thickness of the positive electrode electrolyte interface film is 0.005 μm to 0.15 μm.
[0016] Furthermore, the preparation method further includes: A dry cell is obtained by assembling a positive electrode sheet with a positive electrolyte interface film. The target electrolyte is injected into the dry cell to prepare the cell.
[0017] Furthermore, the target electrolyte includes a lithium salt, and the electrolyte also includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0018] This application also proposes a battery cell, which is prepared by the battery cell preparation method described above.
[0019] This application also proposes a battery comprising the cells described above.
[0020] This application also proposes a vehicle that includes a battery or a cell as described above, the battery or the cell serving as a power source for the vehicle.
[0021] This application also proposes an electrical device comprising a battery or a battery cell as described above, wherein the battery or the battery cell serves as the power supply for the electrical device.
[0022] Compared with related technologies, the embodiments of this application have the following advantages: The battery cell preparation method provided in this application provides a positive electrode electrolyte interface film prepared on the positive electrode sheet before battery cell assembly. This method can form a positive electrode electrolyte interface film on the positive electrode sheet without consuming the active components of the electrolyte in the battery cell. By placing the formation process of the positive electrode electrolyte interface film before battery cell assembly, the positive electrode electrolyte interface film on the positive electrode sheet is already formed before the first charge and discharge of the battery cell. During the first charge and discharge of the battery cell, the positive electrode active material in the positive electrode sheet no longer comes into direct contact with the electrolyte encapsulated in the battery cell due to the blocking effect of the positive electrode electrolyte interface film. This avoids the consumption of active components in the electrolyte during the film formation process of the positive electrode electrolyte interface film, which is beneficial to increasing the amount of effective electrolyte encapsulated inside the battery cell, mitigating the concentration polarization effect of active ion transport during the charge and discharge cycle of the battery cell, reducing the irreversible loss of active ions, improving the electrochemical performance of the battery cell, and extending the cycle life of the battery cell.
[0023] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description
[0024] Figure 1 This is a flowchart of the steps in a method for preparing a battery cell provided in an embodiment of this application. Detailed Implementation
[0025] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] For positive electrode active materials, the stability of their interfacial structure is one of the factors determining the long cycle life of the battery cell. The CEI film is an interfacial film formed by the oxidation reaction between the positive electrode active material and the electrolyte in the positive electrode sheet. During charge-discharge cycles, a high-quality, uniform, and dense CEI film can effectively suppress the side reaction process between the positive electrode active material and the electrolyte, hinder the dissolution of transition metal ions in the positive electrode active material, and improve the interfacial stability between the positive electrode active material and the electrolyte, thereby having a positive impact on the electrochemical performance of the battery cell.
[0027] In related technologies, a CEI film is typically formed at the interface between the positive electrode active material and the electrolyte during the first charge-discharge stage of the cell's formation process after electrolyte injection and encapsulation. The formation of the CEI film is itself an electrochemical decomposition reaction process, requiring the significant consumption of active components in the electrolyte (e.g., film-forming additives, solvents, and lithium salts). This consumption directly leads to a significant reduction in the effective electrolyte content within the cell. The electrolyte content is crucial for maintaining the cell's long cycle life, especially its high-rate performance and high-temperature storage performance. Insufficient electrolyte content exacerbates the concentration polarization effect of active ion transport during charge-discharge cycles, accelerates irreversible ion loss, and may cause localized drying of the positive electrode, ultimately reducing the cell's cycle life.
[0028] Among them, active ions may include, but are not limited to, alkali metal or alkaline earth metal ions such as lithium ions, sodium ions, potassium ions, and magnesium ions.
[0029] To address the aforementioned technical problems, this application provides a method for preparing a battery cell, referring to... Figure 1 The method for preparing the battery cell may specifically include the following steps: Step S101: Before assembling the battery cell, prepare a positive electrode electrolyte interface film on the positive electrode sheet.
[0030] The battery cell fabrication method provided in this application can fabricate a positive electrode electrolyte interface film on any type of positive electrode sheet. In some embodiments, the positive electrode sheet is a positive electrode sheet used to fabricate a battery cell.
[0031] In step S101, before cell assembly, the positive electrode is a bare electrode, comprising a positive current collector and a positive active material layer disposed on the surface of the positive current collector, the positive active material layer comprising positive active material. In step S101, a positive electrolyte interface film is prepared on the positive electrode, specifically by forming the positive electrolyte interface film on the surface of the positive active material of the positive electrode. This allows the formation of the positive electrolyte interface film to be placed before the cell assembly process, eliminating the need to form the positive electrolyte interface film by consuming the active components of the electrolyte in the packaged cell during the first charge-discharge stage. This effectively suppresses the continuous consumption of electrolyte and the structural decay of the positive active material during charge-discharge cycles, which is beneficial for increasing the effective electrolyte storage inside the cell and improving the stability of the positive active material structure in the positive electrode, thereby improving the electrochemical performance of the cell and extending its cycle life.
[0032] In some embodiments, the positive electrode current collector is a metallic material, and its form may include, but is not limited to, metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the positive electrode current collector is a carbon material, and its form may include, but is not limited to, carbon plate, carbon film, carbon cylinder, etc.
[0033] In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, ternary nickel cobalt manganese oxide, ternary nickel cobalt aluminum oxide, layered lithium manganese oxide, spinel lithium manganese oxide, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, and lithium-rich manganese-based positive electrode materials.
[0034] After step S101, the battery cell can be assembled based on the positive electrode sheet with the positive electrolyte interface film to obtain a dry battery cell. Then, based on the dry battery cell, the battery cell is prepared.
[0035] Among them, cell assembly refers to the process of combining the functional components of a cell into a dry cell; in some embodiments, the cell assembly process includes: first, stacking a positive electrode sheet, a separator, and a negative electrode sheet with a positive electrolyte interface film in sequence to form an electrode assembly; then, forming tabs in the electrode assembly through a tab welding process or a tab cutting process to obtain a bare cell; finally, placing the bare cell into an outer packaging aluminum-plastic film and completing the side sealing of the aluminum-plastic film to obtain a dry cell.
[0036] The preparation of a battery cell based on a dry cell may specifically include: first, injecting electrolyte into the dry cell to obtain an electrolyte-filled cell; then, performing formation and aging treatments on the electrolyte-filled cell to obtain the battery cell.
[0037] In related technologies, in order to form a thicker and more stable CEI film at the interface between the positive electrode active material and the electrolyte, thereby improving the interfacial stability between the positive electrode active material and the electrolyte, more stringent formation process conditions are required (e.g., increasing the voltage of the formation process and extending the formation process time). However, this will inevitably lead to excessive consumption of the active components in the electrolyte encapsulated in the battery cell. If milder formation process conditions are adopted in order to preserve the electrolyte level, an effective CEI film may not be formed, causing the interface between the positive electrode active material and the electrolyte to continuously degrade during long-term charge-discharge cycles. The essence of this contradiction lies in placing the CEI film formation process and the requirement to ensure the electrolyte level in the encapsulated battery cell, two completely contradictory processes, in the same sealed cavity. While some related technologies can seek a compromise by optimizing electrolyte formulations (e.g., using more efficient film-forming additives) or refining formation process parameters, they still cannot overcome the electrochemical performance bottleneck caused by the aforementioned contradictions. Consequently, they cannot fundamentally solve the problem of the CEI film formation process consuming large amounts of active components in the electrolyte, leading to a reduction in the effective electrolyte content in the cell, thus restricting the application of high-performance film formation solutions (e.g., highly consumable additives).
[0038] The battery cell preparation method provided in this application prepares a positive electrode electrolyte interface film on the positive electrode sheet before battery cell assembly. This allows for the formation of the positive electrode electrolyte interface film on the positive electrode sheet without consuming the active components of the electrolyte encapsulated in the battery cell. By placing the formation process of the positive electrode electrolyte interface film before battery cell assembly, the positive electrode electrolyte interface film on the positive electrode sheet is already formed before the first charge and discharge of the battery cell. During the first charge and discharge of the battery cell, the positive electrode active material and the electrolyte encapsulated inside the battery cell are effectively isolated by the blocking effect of the positive electrode electrolyte interface film, and the two no longer come into direct contact. This reduces the film-forming reaction between the positive electrode active material and the electrolyte, thereby reducing the consumption of active components in the electrolyte during the film-forming process of the positive electrode electrolyte interface film. This helps to increase the effective electrolyte content encapsulated inside the battery cell, mitigate the concentration polarization effect of active ion transport during charge and discharge cycles, reduce the irreversible loss of active ions, and thus improve the high-rate performance, high-temperature storage performance, and other electrochemical performance of the battery cell, extending the cycle life of the battery cell.
[0039] Furthermore, this application prepares a positive electrode electrolyte interface film on the positive electrode sheet before cell assembly. Placing the film formation reaction of the positive electrode electrolyte interface film before the cell packaging process allows the gas generated during the film formation process to be completely discharged before cell packaging, avoiding the adverse effects of the gas generated during the film formation process on the cell. This application can reduce the gas generation during the cell formation stage by more than 60%, significantly reducing the gas residue inside the cell, reducing the risk of cell expansion, and thus improving the safety and production yield of the cell.
[0040] In one optional embodiment of this application, step S101, which involves preparing a positive electrode electrolyte interface film on the positive electrode sheet before cell assembly, includes: Step S1011: Before assembling the battery cell, immerse the positive active material in the positive electrode sheet in a pretreatment solution to prepare a wetted electrode sheet.
[0041] Step S1012: Microwave treatment is performed on the wetted electrode to prepare a positive electrode electrolyte interface film on the surface of the positive electrode active material of the positive electrode.
[0042] In this embodiment of the application, during the preparation of the positive electrode electrolyte interface film on the positive electrode sheet, the positive active material in the positive electrode sheet can first be immersed in a pretreatment solution to prepare a wetted electrode sheet in step S1011, so that the pretreatment solution uniformly coats the surface of the positive active material. Then, the wetted electrode sheet is microwave-treated in step S1012. The thermal and non-thermal effects of microwaves are used to promote the interfacial reaction between the film-forming components in the pretreatment solution coated on the surface of the positive active material and the positive active material, forming a dense positive electrode electrolyte interface film at the interface between the positive active material and the pretreatment solution. Thus, the preparation of the positive electrode electrolyte interface film on the positive electrode sheet is achieved before the cell assembly. This embodiment of the application immerses the positive electrode active material in the positive electrode sheet in a pretreatment solution, promoting the pretreatment solution to fully and uniformly coat the surface of the positive electrode active material. Combined with the efficient reaction characteristics of subsequent microwave treatment, the uniformity and overall film quality of the positive electrode electrolyte interface film formed on the surface of the positive electrode active material can be improved. Furthermore, by adjusting the type and concentration of film-forming components in the pretreatment solution, as well as the process parameters of microwave treatment, such as microwave power, duration, and temperature, the film thickness of the positive electrode electrolyte interface film can be flexibly and precisely controlled. This improves the operability of this embodiment of the application, and the process flow is simple, requiring no complex equipment or operating steps. It can improve the efficiency of preparing the positive electrode electrolyte interface film on the positive electrode sheet, making it easy to scale up the process and mass-produce, providing a new approach for the preparation of high-performance battery cells.
[0043] Specifically, before step S1011, the film-forming components of the positive electrode electrolyte interface film can be dissolved in a target solvent to obtain a pretreatment solution. The pretreatment solution includes the film-forming components of the positive electrode electrolyte interface film and the target solvent. The film-forming components refer to components that can undergo an interfacial reaction with the positive electrode active material and deposit on the surface of the positive electrode active material to form a positive electrode electrolyte interface film. The target solvent is used to dissolve the film-forming components. In this embodiment, the target solvent can be any type of solvent capable of dissolving the film-forming components.
[0044] In some embodiments, the film-forming component may include at least one of lithium salt compounds, carbonate compounds, sulfate compounds, fluorine-containing film-forming additives, phosphorus-based film-forming additives, and boron-based film-forming additives; the target solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC).
[0045] In step S1011, the positive electrode active material in the positive electrode sheet can be immersed in the pretreatment solution. After the pretreatment solution has fully and uniformly penetrated the surface of the positive electrode active material, the positive electrode sheet can be removed from the pretreatment solution using polytetrafluoroethylene (PTFE) tweezers or stainless steel tweezers to obtain a wetted electrode sheet. In some embodiments, the portion of the positive electrode sheet containing the positive electrode active material layer can be immersed in the pretreatment solution; in some embodiments, the entire positive electrode sheet can be completely immersed in the pretreatment solution.
[0046] In the impregnation electrode, the pretreatment solution remains on the surface of the positive electrode active material of the positive electrode.
[0047] In some embodiments, the temperature at which the positive active material in the positive electrode sheet is immersed in the pretreatment solution is room temperature (20°C~30°C).
[0048] In step S1012, the wetted electrode sheet taken from the pretreatment solution can be transferred to a microwave device. The microwave device generates microwaves to treat the wetted electrode sheet. Through the synergistic effect of the thermal and non-thermal effects of microwaves, the positive electrode active material, due to its own polarity, will have a dipole interaction with the polar film-forming components in the pretreatment solution that are coated on its surface, thereby triggering a directional redox reaction. Relying on the uniform coating and distribution of the film-forming components in the pretreatment solution on the surface of the positive electrode active material, the film-forming components are uniformly formed at the positive electrode interface under the drive of the dipole interaction. Finally, a dense, uniform positive electrode electrolyte interface film with excellent ion conductivity is formed in situ on the surface of the positive electrode active material.
[0049] In step S1012, the gas atmosphere for microwave treatment can be determined based on the stability of the film-forming components in the pretreatment solution. In some embodiments, the film-forming components readily decompose with oxygen and / or water molecules in the air. In this scenario, the gas atmosphere for microwave treatment is a vacuum or an inert gas, which may include, but is not limited to, He, Ar, and N2. This helps reduce side reactions of the film-forming components and improves the film-forming efficiency and quality of the cathode electrolyte interface film. In some embodiments, the film-forming components have high stability in air. In step S1012, the gas atmosphere for microwave treatment can be determined to be air. This ensures the quality of the cathode electrolyte interface film while reducing the process complexity and cost of microwave treatment.
[0050] In some embodiments, during the microwave treatment of the impregnated electrode, the power, duration, and temperature within the microwave device cavity can be flexibly adjusted according to the type of positive electrode active material, the required ratio of film-forming components, and the thickness requirements of the positive electrode electrolyte interface film. This allows for precise control of the thickness, density, and interfacial bonding of the positive electrode electrolyte interface film, enabling the prepared positive electrode electrolyte interface film to effectively cover the active sites on the surface of the positive electrode active material, suppress side reaction processes between the positive electrode active material and the electrolyte, improve the electrochemical performance of the battery cell, and extend the cycle life of the battery cell.
[0051] In one optional embodiment of this application, the film-forming components include vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), 1,3,2-dioxathiolane 2,2-dioxide (DTD), and lithium bis(oxalato)borate (LiPO2F2). At least one of Bis(oxalato)borate (LiBOB), including vinylene carbonate, fluoroethylene carbonate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, vinyl sulfate, and lithium bis(oxalato)borate, can chemically react with the positive electrode active material at the interface between the pretreatment solution and the positive electrode active material to form a well-covering positive electrode electrolyte interface film on the surface of the positive electrode active material. This effectively passivates the active sites on the surface of the positive electrode active material, blocks direct contact between the electrolyte in the battery cell and the positive electrode active material, inhibits the side reaction process between the positive electrode active material and the electrolyte, reduces the irreversible loss of active lithium ions, and improves the interfacial stability between the positive electrode active material and the electrolyte. Among these, vinylene carbonate and fluoroethylene carbonate can... To construct a positive electrode electrolyte interface membrane with good interfacial adhesion, fluoroethylene carbonate can introduce fluorine-containing functional groups to improve the compactness and oxidation resistance of the positive electrode electrolyte interface membrane. Lithium difluorosulfonyl imide can provide lithium ions and optimize the ion conduction efficiency of the positive electrode electrolyte interface membrane, while improving the dispersion uniformity of the film-forming components. Lithium difluorophosphate can generate inorganic phases such as Li3PO4 and LiF, enhancing the mechanical strength and cycle resistance of the positive electrode electrolyte interface membrane. Ethylene sulfate can strengthen the oxidation resistance of the positive electrode electrolyte interface membrane, inhibit oxygen evolution of the positive electrode active material and deep oxidation of the electrolyte. Lithium bis(oxalate-borate) can improve the interfacial bonding force between the positive electrode electrolyte interface membrane and the positive electrode active material, while optimizing the high-temperature stability of the positive electrode electrolyte interface membrane.
[0052] In one optional embodiment of this application, the concentration of the film-forming component in the pretreatment solution is 0.1wt% to 10wt%. Within this range, not only can the uniformity of dissolution and dispersion of the film-forming component in the target solvent be improved, and the stability of the pretreatment solution be enhanced, but sufficient film-forming material can also be provided for the film-forming reaction of the positive electrode electrolyte interface film. Furthermore, the thickness of the positive electrode electrolyte interface film is positively correlated with the concentration of the film-forming component. By controlling the concentration of the film-forming component within the range of 0.1wt% to 10wt%, the film thickness and density of the positive electrode electrolyte interface film can be precisely controlled, taking into account both the film-forming effect and the raw material utilization rate, reducing film-forming defects of the positive electrode electrolyte interface film, improving the film-forming quality of the positive electrode electrolyte interface film, thereby improving the interface stability of the positive electrode sheet, reducing the interface side reactions of the battery cell in the subsequent formation process and charge-discharge cycle process, improving the electrochemical performance of the battery cell, and extending the cycle life of the battery cell. In some embodiments, the concentration of the film-forming component in the pretreatment solution can be one of 0.1 wt%, 3 wt%, 6 wt%, 8 wt%, and 10 wt%, or any value between two of them.
[0053] The concentration of the film-forming component refers to the mass percentage of the film-forming component in the pretreatment solution.
[0054] In one optional embodiment of this application, the concentration of the film-forming component in the pretreatment solution is 1 wt% to 5 wt%. Within this range, it is possible to reduce film-forming defects in the positive electrode electrolyte interface film, improve the film-forming quality of the positive electrode electrolyte interface film, and simultaneously improve the precision of controlling the film thickness and density of the positive electrode electrolyte interface film. In some embodiments, the concentration of the film-forming component in the pretreatment solution can be one of 1 wt%, 2 wt%, 3 wt%, 4 wt%, and 5 wt%, or any value between two of these.
[0055] In one optional embodiment of this application, step S1011, which involves immersing the positive active material in the positive electrode sheet in a pretreatment solution to prepare a wetted electrode sheet, includes: Step A11: Immerse the positive electrode active material in the positive electrode sheet in the pretreatment solution.
[0056] Step A12: When the positive electrode active material is immersed in the pretreatment solution for a first time, the positive electrode sheet wetted with the pretreatment solution is taken out of the pretreatment solution and suspended in the air until the suspension time reaches a second time or no liquid drips from the surface of the positive electrode sheet within a third time, thus obtaining the wetted electrode sheet.
[0057] In this embodiment, after the positive electrode active material is immersed in the pretreatment solution for a first duration, the positive electrode sheet wetted with the pretreatment solution is removed from the pretreatment solution and suspended in the air until the suspension time reaches a second duration or no liquid drips from the surface of the positive electrode sheet within a third duration, thus obtaining a wetted electrode sheet. This can improve the uniformity of the pretreatment solution adhering to the surface of the positive electrode active material in the same wetted electrode sheet, and improve the consistency of the amount of pretreatment solution adhering to the surface of the positive electrode active material in different wetted electrode sheets. This is beneficial to improving the synchronicity and uniformity of the film-forming reaction occurring on the surface of the positive electrode active material during microwave treatment, thereby improving the thickness, density, and uniformity of the ion conduction performance of the positive electrode electrolyte interface film formed on the surface of the positive electrode active material. Therefore, it can not only improve the film-forming quality of the positive electrode electrolyte interface film in a single positive electrode sheet, but also help to achieve standardization and consistency of the film-forming effect of different wetted electrode sheets, and improve the batch stability of the positive electrode sheet products.
[0058] Specifically, in step A11, the positive active material in the positive electrode sheet can be immersed in the pretreatment solution with reference to the detailed description of step S1011, and the timing starts at the moment when the positive active material in the positive electrode sheet is immersed in the pretreatment solution.
[0059] In step A12, after the positive electrode active material has been immersed in the pretreatment solution for a first time, the positive electrode sheet immersed in the pretreatment solution can be removed from the pretreatment solution using polytetrafluoroethylene tweezers or stainless steel tweezers, and the positive electrode sheet removed from the pretreatment solution can be suspended and left to stand to promote the dripping of excess pretreatment solution adhering to the positive electrode sheet.
[0060] In some embodiments, when the suspension and resting time reaches a second duration, the positive electrode sheet after suspension and resting can be identified as a wetted electrode sheet.
[0061] In some embodiments, if no liquid drips from the surface of the positive electrode sheet during the suspension and static process within a third time period, the positive electrode sheet after suspension and static process can be identified as a wetted electrode sheet.
[0062] In one optional embodiment of this application, in step A12, the first duration is 5 min to 30 min. Within this range, it is beneficial to ensure that the pretreatment solution fully and uniformly penetrates into the pore structure of the positive electrode active material layer, promotes sufficient contact between the film-forming components in the pretreatment solution and the active sites on the surface of the positive electrode active material, and facilitates their adhesion to the surface of the positive electrode active material. This lays the foundation for forming a uniformly thick and fully covered positive electrode electrolyte interface film on the surface of the positive electrode active material. In some embodiments, the first duration can be one of 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min, or a range between any two.
[0063] In one optional embodiment of this application, in step A12, the second duration is greater than or equal to 30 minutes. Within this range, it can be ensured that the excess pretreatment solution attached to the positive electrode sheet can be fully dripped off, thereby improving the uniformity of the pretreatment solution attached to the surface of the positive electrode active material in the same wetted electrode sheet, and improving the consistency of the amount of pretreatment solution attached to the surface of the positive electrode active material in different wetted electrode sheets.
[0064] In one optional embodiment of this application, in step A12, the third duration is 1 min to 5 min. Within this range, excess pretreatment solution adhering to the positive electrode sheet can be fully dripped off, improving the uniformity of the pretreatment solution adhering to the surface of the positive active material in the same wetting electrode sheet, and improving the consistency of the amount of pretreatment solution adhering to the surface of the positive active material in different wetting electrode sheets, while also improving the preparation efficiency of the wetting electrode sheet. In some embodiments, the third duration can be one of 1 min, 2.5 min, 3 min, 4 min, 4.5 min, and 5 min, or a range between any two.
[0065] In one optional embodiment of this application, in step S1012, the power of microwave treatment of the impregnated electrode is 100W~1000W, and the duration of microwave treatment is 5min~20min. The thickness of the positive electrode electrolyte interface film is positively correlated with the power and duration of microwave treatment. If the power of microwave treatment is too low and / or the duration of microwave treatment is too short, the thickness of the positive electrode electrolyte interface film formed on the surface of the positive electrode active material will be too small, resulting in a decrease in density and failure to effectively passivate and completely cover the active sites on the surface of the positive electrode active material. If the power of microwave treatment is too high and / or the duration of microwave treatment is too long, the film-forming reaction will be over-progressed, resulting in an excessively thick positive electrode electrolyte interface film. This will not only hinder the active ion transport process between the positive electrode active material and the electrolyte, leading to an increase in the interfacial impedance of the positive electrode active material, but will also consume a large number of active sites on the surface of the positive electrode active material during the over-film formation process, destroying the microstructure of the positive electrode active material and causing a decrease in the structural stability of the positive electrode active material. In this embodiment, the microwave treatment power is controlled within the range of 100W to 1000W, and the microwave treatment duration is controlled within the range of 5min to 20min. This not only forms a uniform and complete positive electrode electrolyte interface film on the surface of the positive electrode active material, effectively passivating the active sites on the surface of the positive electrode active material and improving the interfacial stability between the positive electrode active material and the electrolyte, but also effectively protects the microstructure of the positive electrode active material, improves the structural stability of the positive electrode active material, and improves the ion conduction performance of the positive electrode electrolyte interface film, ensuring the efficient transport of active ions in the positive electrode active material, thereby improving the electrochemical performance of the battery cell and extending the cycle life of the battery cell.
[0066] In some embodiments, the power for microwave treatment of the impregnated electrode can be a range of 100W, 300W, 500W, 800W, 900W, and 1000W, or any combination thereof. In some embodiments, the duration of microwave treatment of the impregnated electrode can be a range of 5min, 9min, 12min, 16min, 18min, and 20min, or any combination thereof.
[0067] In some embodiments, the temperature for microwave treatment of the impregnated electrode is room temperature (20°C~30°C), which not only forms a uniform and fully covered positive electrode electrolyte interface film on the surface of the positive electrode active material, but also reduces the energy consumption of the cell manufacturing process, thereby reducing the manufacturing cost of the cell.
[0068] In one optional embodiment of this application, step S1012, which involves microwave treatment of the impregnated electrode to prepare a positive electrode electrolyte interface film on the surface of the positive electrode active material of the positive electrode, includes: Step B11: Microwave the impregnated electrode to obtain a microwave electrode.
[0069] Step B12: Immerse the positive electrode active material in the microwave electrode sheet in the target solvent.
[0070] Step B13: After the positive electrode active material has been immersed in the target solvent for a fourth time, the microwave electrode sheet immersed in the target solvent is removed from the target solvent and suspended in the air until the suspension time reaches a fifth time or no liquid drips from the surface of the microwave electrode sheet within a sixth time, thus obtaining a cleaned electrode sheet.
[0071] Step B14: Dry the cleaned electrode to obtain a positive electrode electrolyte interface film formed on the surface of the positive electrode active material of the positive electrode.
[0072] In this embodiment, during the formation of the positive electrode electrolyte interface film on the surface of the positive electrode active material of the positive electrode sheet, the wetted electrode sheet can first be microwave-treated in step B11 to obtain a microwave electrode sheet, thereby forming an initial positive electrode electrolyte interface film on the surface of the positive electrode active material. Then, the microwave electrode sheet is cleaned through the corresponding operations in steps B12 and B13, which can fully dissolve and wash out the unreacted film-forming components on the surface and in the pores of the positive electrode active material, which is beneficial to improving the cleanliness of the positive electrode sheet and avoiding the residual film-forming components from reacting during subsequent cell preparation and charge-discharge cycling. The side reactions are eliminated, and the cleaned electrode is dried with B14 to obtain a dense and clean positive electrode electrolyte interface film formed on the surface of the positive electrode active material. The embodiments of this application can not only form a uniform and completely covered positive electrode electrolyte interface film on the surface of the positive electrode active material to improve the interfacial stability between the positive electrode active material and the electrolyte, but also remove residual film-forming components in the positive electrode active material, optimize the surface microstate of the positive electrode active material, improve the ion conduction performance of the positive electrode electrolyte interface film, thereby improving the electrochemical performance of the battery cell and extending the cycle life of the battery cell.
[0073] In step B11, the impregnated electrode can be microwave-treated with reference to the detailed description of step S1012 to obtain a microwave electrode.
[0074] In step B12, the positive electrode active material in the microwave electrode sheet can be immersed in the target solvent to allow the target solvent to fully and uniformly penetrate the surface of the positive electrode active material, thereby fully dissolving and washing out any unreacted film-forming components on the surface of the positive electrode active material. In this embodiment, timing can begin when the positive electrode active material in the microwave electrode sheet is immersed in the target solvent.
[0075] The target solvent may include at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0076] When the positive electrode active material is immersed in the target solvent for a period of four, step B13 is performed to remove the microwave electrode sheet immersed in the target solvent from the target solvent using polytetrafluoroethylene tweezers or stainless steel tweezers, and to suspend the microwave electrode sheet removed from the target solvent in the air to promote the dripping of excess target solvent adhering to the microwave electrode sheet.
[0077] In some embodiments, the fourth time period is 5 min to 30 min, which helps to ensure that the target solvent fully and uniformly penetrates the surface of the positive electrode active material, promoting the complete dissolution and washing out of the unreacted film-forming components on the surface of the positive electrode active material. In some embodiments, if the suspension and standing time reaches a fifth time period, the microwave electrode sheet after suspension and standing can be identified as a cleaned electrode sheet. The fifth time period is greater than or equal to 30 min, which ensures that excess target solvent adhering to the microwave electrode sheet drips off completely, improving the consistency of the drying degree of different positive electrode sheets. In some embodiments, if no liquid drips from the surface of the microwave electrode sheet during the suspension and standing process within a sixth time period, the microwave electrode sheet after suspension and standing can be identified as a cleaned electrode sheet. The sixth time period is 1 min to 5 min, which ensures that excess target solvent adhering to the microwave electrode sheet drips off completely, improving the consistency of the drying degree of different positive electrode sheets, and simultaneously improving the preparation efficiency of the cleaned electrode sheet.
[0078] In step B14, the cleaned electrode can be transferred to a vacuum drying oven and vacuum dried at 60℃~80℃ for 8h~12h to remove the residual target solvent in the positive electrode and obtain the positive electrode electrolyte interface film formed on the surface of the positive electrode active material of the positive electrode.
[0079] This application utilizes microwave induction to construct a uniform and dense positive electrode electrolyte interface film on the surface of the positive electrode active material. Combined with the clean interface resulting from the cleaning effect of the target solvent, it effectively suppresses the continuous decomposition of the electrolyte and the structural degradation of the positive electrode active material during charge-discharge cycles. The battery cell prepared based on the positive electrode sheet of this application retains a capacity retention rate of over 94% after 500 charge-discharge cycles, demonstrating excellent lifespan performance. Furthermore, the "immersion-microwave-cleaning" process provided in this application is mild, simple, and uses safe and controllable reagents and solvents. It achieves independent and precise control of the positive electrode interface reaction, while eliminating the need for expensive additives in the target electrolyte, simplifying the electrolyte formulation and facilitating scale-up and large-scale production, thus providing a new approach for the manufacture of high-performance battery cells.
[0080] In one optional embodiment of this application, the thickness of the positive electrode electrolyte interface film is 0.005 μm to 0.15 μm. Within this range, not only can the role of the positive electrode electrolyte interface film in suppressing the side reaction process between the positive electrode active material and the electrolyte and improving the interfacial stability between the positive electrode active material and the electrolyte be fully utilized, but it can also avoid the positive electrode electrolyte interface film being too thick and hindering the active ion transport process between the positive electrode active material and the electrolyte. This is beneficial to improving the ion conduction performance of the positive electrode electrolyte interface film and increasing the transport efficiency of active ions in the positive electrode active material. In some embodiments, the thickness of the positive electrode electrolyte interface film can be one of 0.005 μm, 0.03 μm, 0.06 μm, 0.09 μm, 0.12 μm, and 0.15 μm, or any value between two of them.
[0081] In one optional embodiment of this application, the method for preparing the battery cell provided in this application may further include the following steps: Step S102: Assemble the battery cell based on the positive electrode sheet with the positive electrolyte interface film to obtain a dry battery cell.
[0082] Step S103: Inject the target electrolyte into the dry cell to prepare the cell.
[0083] In this embodiment, after the positive electrode electrolyte interface film is prepared on the positive electrode sheet in step S101, the battery cell can be prepared based on the positive electrode sheet with the prepared positive electrode electrolyte interface film in steps S102 and S103. In this embodiment, the formation process of the positive electrode electrolyte interface film is placed before the battery cell assembly process. Before the first charge and discharge of the battery cell, the positive electrode electrolyte interface film on the positive electrode sheet has already been formed. During the first charge and discharge of the battery cell, under the blocking effect of the positive electrode electrolyte interface film, the positive active material in the positive electrode sheet no longer comes into direct contact with the electrolyte encapsulated in the battery cell, so the formation process of the positive electrode electrolyte interface film will not occur. This avoids the consumption of active components in the electrolyte by the film formation process of the positive electrode electrolyte interface film, which is conducive to increasing the amount of effective electrolyte encapsulated inside the battery cell, slowing down the concentration polarization effect of active ion transport during the charge and discharge cycle of the battery cell, reducing the irreversible loss of active ions, which is conducive to improving the electrochemical performance of the battery cell and extending the cycle life of the battery cell.
[0084] In step S102, firstly, the positive electrode sheet, separator, negative electrode sheet, and separator with the positive electrolyte interface membrane are stacked sequentially, and this process is repeated to form a multi-layer stacked structure. Then, the stacked structure is fixed with tape, and the positive electrode tab and negative electrode tab are welded on respectively. Finally, the stacked structure with welded tabs is put into a punched aluminum-plastic film packaging bag, and the long side of the aluminum-plastic film is initially sealed by heat sealing, leaving one side liquid injection port, to obtain a dry cell.
[0085] In some embodiments, the heat sealing temperature can be 150°C to 200°C, the heat sealing pressure can be 0.5MPa to 2.0MPa, and the heat sealing time can be 3s to 10s.
[0086] In step S103, firstly, the target electrolyte is injected into the dry cell through the pre-reserved injection port to obtain an injected cell. The injection volume of the target electrolyte can be determined according to the cell's capacity and porosity. In some embodiments, the injection volume of the target electrolyte is 2.5 g / Ah to 5 g / Ah. Then, the injected cell is placed at room temperature for 12 h to 48 h to ensure that the target electrolyte fully wets the entire cell. Next, the injected cell after standing is placed in a vacuum sealing machine, and the pre-reserved injection port is heat-sealed under a vacuum of -0.08 MPa to -0.10 MPa to obtain a packaged cell. Afterward, the packaged cell is placed in an environment at 25℃±5℃ for formation. During this process, a stable solid electrolyte interfacial film is mainly formed on the surface of the negative electrode active material. After the formation process is completed, the packaged cells are left to age for 24 to 72 hours. Finally, the aged packaged cells are subjected to necessary tests, capacity testing and other subsequent processes to obtain the cells.
[0087] In some embodiments, the temperature for heat-sealing the reserved injection port is 150°C to 200°C, the pressure for heat-sealing the reserved injection port is 0.5MPa to 2.0MPa, and the duration for heat-sealing the reserved injection port is 3s to 10s.
[0088] In some embodiments, the method for forming the packaged battery cell includes: using a charge-discharge device to perform an initial charge on the packaged battery cell with a small current of 0.02C to 0.1C. The charging cut-off voltage can be determined according to the type of positive electrode active material. In some embodiments, the charging cut-off voltage can be 3.0V to 4.2V.
[0089] The target electrolyte acts as a conductor of ions between the positive and negative electrodes. In some embodiments, the concentration of the target electrolyte is 0.8 mol / L to 1.5 mol / L.
[0090] In one optional embodiment of this application, the target electrolyte includes a lithium salt, and the electrolyte further includes at least one selected from ethylene carbonate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate. In this embodiment, the target electrolyte injected into the dry cell may only include a lithium salt and a target solvent (at least one selected from ethylene carbonate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate). The target electrolyte may no longer contain the film-forming components from the pretreatment solution, which simplifies the formulation system of the target electrolyte, reduces the preparation cost and raw material control difficulty, and avoids the problem of excessive film formation at the positive electrode electrolyte interface caused by repeated addition of film-forming components to the electrolyte. This improves the utilization rate of the target electrolyte, reduces side reactions within the cell, further improves the cycle stability, rate performance, and storage performance of the cell, and helps extend the cycle life of the cell.
[0091] In some embodiments, lithium salts include, but are not limited to, lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroantimonyate (LiSbF6), lithium bis(trifluoromethanesulfonate imide) (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium iodide (LiI), and lithium magnesium bis(fluorosulfonyl)imide (Li2Mg(N(SO2CF3)2)2).
[0092] This application also provides a battery cell, which is prepared by the battery cell preparation method described above. In some embodiments, the battery cell may be a liquid battery cell.
[0093] In the battery cell, the positive electrode active material layer in the positive electrode sheet also includes a conductive agent and a binder. In some embodiments, the conductive agent includes at least one of graphite, hard carbon, soft carbon, carbon nanotubes (CNTs), graphene, porous carbon, superconducting carbon black (Super P), acetylene black, and furnace black; in some embodiments, the binder includes polytetrafluoroethylene, polyvinylidene fluoride (PVDF), silicone rubber, polymerized styrene-butadiene rubber (SBR), hydrogenated acrylonitrile-butadiene rubber (HNBR), boronized polyethylene glycol, cellulose, cellulose esters, cellulose ethers, nitrocellulose (NC), carboxyalkyl cellulose, cellulose salts, sodium carboxymethyl cellulose (CMC) and cellulose salt derivatives, polyacrylic acid (PAA), polyamide (PAI), and polyvinyl alcohol (PEA). At least one of alcohol (PVA), polyethyleneimine (PEI), and polyimide (PI).
[0094] In some embodiments, the positive electrode sheet is prepared by a wet process: 1) The components used to prepare the positive electrode sheet, such as the positive active material, conductive agent, binder, and any other components, are dispersed in a solvent such as N-methylpyrrolidone (NMP), and stirred for 60 min to 120 min under vacuum conditions of -0.08 MPa to -0.10 MPa and a rotation speed of 800 rpm to 1500 rpm to obtain a uniform, particle-free positive electrode slurry with a viscosity in the range of 3000 mPa·s to 8000 mPa·s; 2) A metal foil with a thickness of 10 μm to 20 μm is provided as the positive electrode current collector, and its surface is cleaned and dried to remove oil and oxides. Optionally, the positive electrode current collector is further... 1) Perform corona treatment or coat a conductive coating to enhance the adhesion between the positive electrode slurry and the positive electrode current collector; 2) Apply the positive electrode slurry evenly to at least one side of the positive electrode current collector using a transfer coating machine or an extrusion coating machine, controlling the coating speed and slit gap to achieve a wet film thickness of 100μm~300μm after coating; 3) Send the coated wet electrode sheet into a drying oven for segmented drying: the first segment is pre-dried at 60℃~80℃ for 2min~5min to evaporate most of the solvent, and the second segment is vacuum dried at 100℃~130℃ for 6h~12h to completely remove residual organic solvents and form a dry positive electrode active material layer; 4) Roll the dried electrode sheet through a double-roller press, controlling the pressure, roll gap, and roll speed of the press to achieve a compaction density of 2.5g / cm³ for the positive electrode active material layer. 3 ~4.0g / cm 3 6) The thickness of the rolled electrode sheet is reduced by 10% to 30% compared with that before rolling; 7) The rolled continuous electrode sheet is cut into the required width by a slitting machine according to the design requirements of the cell model, and then cut into single positive electrode sheets of specified size by a cutting machine; 8) The cut positive electrode sheets are placed in a vacuum oven and baked at 120℃ to 180℃ for 4h to 12h to further remove the trace amount of moisture absorbed by the positive electrode sheet during the preparation process, and finally obtain the positive electrode sheet that needs to be prepared by the above step S101 to prepare the positive electrolyte interface film.
[0095] In some embodiments, the negative electrode in the battery cell is a lithium metal sheet or a lithium alloy sheet, with a thickness of 0.01 μm to 100 μm. The lithium alloy Li-M can be an alloy formed from lithium metal and at least one of the following substances: gold (Au), indium (In), magnesium (Mg), zinc (Zn), chromium (Cr), nickel (Ni), molybdenum (Mo), tungsten (W), vanadium (V), titanium (Ti), niobium (Nb), zirconium (Zr), cobalt (Co), manganese (Mn), aluminum (Al), copper (Cu), boron (B), silver (Ag), tin (Sn), silicon (Si), carbon (C), and phosphorus (P), wherein the lithium metal content is 1 wt% to 99 wt%.
[0096] In some embodiments, the negative electrode sheet in the battery cell includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The negative active material layer includes a negative active material, a conductive agent, and a binder.
[0097] In some embodiments, the negative electrode active material may include, but is not limited to, at least one of lithium metal (Li) or lithium metal alloy (Li-M), artificial graphite, natural graphite, modified graphite, fast-charging graphite, soft carbon, hard carbon, fumed silicon carbide, ground silicon carbide, silicon suboxide, pre-lithiated silicon suboxide, and pre-magnesiated silicon suboxide; wherein, the lithium metal alloy (Li-M) may be an alloy formed by lithium metal and at least one of Au, In, Mg, Zn, Cr, Ni, Mo, W, V, Ti, Nb, Zr, Co, Mn, Al, Cu, B, Ag, Sn, Si, C, P, etc., wherein the content of lithium metal is 1wt% to 99wt%.
[0098] In some embodiments, the conductive agent in the negative electrode active material layer includes at least one of Super-P, vapor-grown carbon fiber (VGCF), and CNT. In some embodiments, the binder in the negative electrode active material layer includes at least one of PVDF, SBR, nitrile butadiene rubber (NBR), butadiene rubber (BR), CMC, and PAA.
[0099] The negative electrode current collector is selected from a metallic material that can conduct electrons. In some embodiments, the negative electrode current collector includes at least one of Al, Ni, Sn, Cu, and stainless steel. In some embodiments, the negative electrode current collector is selected from copper foil.
[0100] In some embodiments, the method for preparing the negative electrode sheet includes: coating a negative electrode slurry made of a negative electrode active material, a conductive agent, a binder, and any other components onto a negative electrode current collector, and then drying and cold-pressing it to form a negative electrode sheet. The solvent may be an aqueous solvent, but is not limited thereto.
[0101] In some embodiments, the diaphragm includes a base membrane, which may be at least one of polyethylene (PE) diaphragm, polypropylene (PP) diaphragm, nonwoven fabric diaphragm, and PI diaphragm.
[0102] In some embodiments, the base film has a coating on at least one side; the coating comprises: an oxide solid electrolyte, an alkaline oxide, and a polymer adhesive; the oxide solid electrolyte and the alkaline oxide are dispersed in the polymer adhesive; the alkaline oxide includes at least one of alumina and boehmite. The oxide solid electrolyte includes at least one of NASICON-type solid electrolyte, garnet-type solid electrolyte, and perovskite-type solid electrolyte.
[0103] The above-described battery cell embodiments are prepared using the same method and achieve the same technical effects. To avoid repetition, they will not be described again here. For relevant details, please refer to the description in the embodiment section of the battery cell preparation method.
[0104] This application also provides a battery, which includes the cells described above.
[0105] The battery can be any one of cylindrical batteries, pouch batteries, or prismatic batteries. The battery includes a cell retainer and multiple cells, the cell retainer being used to secure the multiple cells after they are connected.
[0106] The battery embodiments described above include the aforementioned battery cells and achieve the same technical effects. To avoid repetition, they will not be repeated here. For relevant details, please refer to the description in the battery cell embodiment section.
[0107] This application also proposes a vehicle that includes a battery or a cell as described above, the battery or the cell serving as a power source for the vehicle.
[0108] In some embodiments, the vehicle may be a motor vehicle, such as a passenger car, a truck or its derivatives; it may also be a special vehicle, such as a tractor, an excavator, a fire truck, an ambulance, etc.; it may also be a water vehicle, such as an amphibious vehicle; or it may be a rail transit vehicle, such as a train, a subway, a tram, etc.
[0109] The vehicle embodiments described above include the aforementioned battery and achieve the same technical effects. To avoid repetition, they will not be repeated here. For relevant details, please refer to the description in the battery embodiment section.
[0110] This application also proposes an electrical device comprising the aforementioned battery or the aforementioned battery cell, wherein the battery or the battery cell serves as the power supply for the electrical device.
[0111] The battery can be a power source for the electrical device or an energy storage unit for the electrical device. Electrical devices can include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be, for example, mobile phones, laptops, etc.; electric vehicles can be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.
[0112] The above-described embodiment of the electrical device includes the aforementioned battery and achieves the same technical effect. To avoid repetition, it will not be described again here. For relevant details, please refer to the description in the battery embodiment section.
[0113] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0114] The present application will be described in detail below through embodiments.
[0115] Example 1 (1) Preparation of the positive electrode sheet: First, high-nickel ternary material, Super P, and polyvinylidene fluoride were placed in a vacuum mixer at a mass ratio of 90:5:5. The organic solvent N-methylpyrrolidone was added, and the mixture was stirred for 90 minutes under a vacuum of -0.09 MPa and a rotation speed of 1000 rpm to obtain a positive electrode slurry with a viscosity of 5000 mPa·s. Then, after cleaning and drying a 15 μm thick aluminum foil surface, the positive electrode slurry was uniformly coated onto both sides of the aluminum foil using a transfer coating machine, resulting in a wet film thickness of 200 μm. Next, the coated wet electrode was sent to a drying oven for segmented drying: the first segment was pre-dried at 70℃ for 3 minutes, and the second segment was vacuum-dried at 110℃ for 8 hours to form a dried positive electrode active material layer. Finally, the dried electrode was rolled using a double-roller press, controlling the pressure, roll gap, and roll speed of the press to achieve a compaction density of 3 g / cm³ for the positive electrode active material layer. 3 Finally, the continuous electrode sheet after rolling is cut and dried to obtain the positive electrode sheet.
[0116] (2) Preparation of the positive electrode electrolyte interface film: First, in a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), the film-forming components VC and FEC were dissolved in DMC solvent and stirred thoroughly until completely dissolved to obtain a homogeneous and clear pretreatment solution. The concentration of VC in the pretreatment solution was 2 wt%, and the concentration of FEC was 2 wt%. Then, in the glove box, the positive electrode prepared in step (1) was completely immersed in the pretreatment solution, and the immersion temperature was controlled at room temperature (25°C) for 15 min. Then, the positive electrode wetted with the pretreatment solution was removed from the pretreatment solution using stainless steel tweezers and suspended for 30 min until no droplets were observed on the surface of the positive electrode to obtain the wetted electrode. The electrodes were prepared by first soaking them in a glove box and then transferring them to a microwave oven. The microwave electrodes were then microwaved at 800W for 15 minutes to obtain microwave electrodes. Next, the microwave electrodes were completely immersed in DMC solvent for 15 minutes. Then, stainless steel tweezers were used to remove the DMC-soaked electrodes from the solvent and allowed to stand for 30 minutes until no liquid droplets were visible on the surface of the electrodes, resulting in cleaned electrodes. Finally, the cleaned electrodes were transferred to a vacuum drying oven and vacuum dried at 70℃ for 10 hours to obtain a positive electrode electrolyte interface film formed on the surface of the positive electrode active material. The thickness of the positive electrode electrolyte interface film was 0.05 μm.
[0117] (3) Preparation of negative electrode sheet: A negative electrode sheet is provided, which includes a copper foil and a graphite negative electrode active material layer coated on both sides of the copper foil. After vacuum drying, it is transferred to a glove box for later use.
[0118] (4) Preparation of the diaphragm: Cut the PP single-layer porous diaphragm to the size that matches the positive and negative electrode sheets, and place it in a glove box for later use.
[0119] (5) Preparation of electrolyte: In an argon-atmospheric glove box, LiPF6 was dissolved in a compound solvent of EC, EMC and DMC to prepare a target electrolyte with a LiPF6 concentration of 1 mol / L, wherein the mass ratio of EC, EMC and DMC was 1:1:1.
[0120] (6) Preparation of dry cell: First, the positive electrode sheet prepared with the positive electrolyte interface membrane in step (2), the separator prepared in step (4), the negative electrode sheet prepared in step (3), and the separator prepared in step (4) are stacked in sequence, and this process is repeated to form a multi-layer stacked structure. Then, the stacked structure is fixed with tape, and the positive electrode tab and the negative electrode tab are welded on respectively. Finally, the stacked structure with the welded tabs is put into a punched aluminum-plastic film packaging bag, and the long side of the aluminum-plastic film is initially sealed by heat sealing, leaving one side liquid injection port to obtain a dry cell. The heat sealing temperature is 180℃, the heat sealing pressure is 1MPa, and the heat sealing time is 6s.
[0121] (7) Cell fabrication: First, the target electrolyte prepared in step (5) is injected into the dry cell through the pre-reserved injection port to obtain the liquid-filled cell. The injection volume of the target electrolyte is 4.5 g / Ah. Then, the liquid-filled cell is placed at room temperature (25℃) and left to stand for 24 h. Then, the liquid-filled cell after standing is placed in a vacuum sealing machine and the pre-reserved injection port is heat-sealed under a vacuum of -0.09 MPa to obtain the packaged cell. The heat-sealing temperature is 180℃, the heat-sealing pressure is 1 MPa, and the heat-sealing time is 6 s. After that, the packaged cell is placed in an environment with a temperature of 25℃±5℃ and charged to 4.2V with a constant current of 0.05C for formation. After the formation is completed, the packaged cell is left to stand and age at room temperature (25℃) for 48 h to obtain the cell.
[0122] Example 2 The difference between Example 2 and Example 1 is as follows: In step (2), the film-forming component LiPO2F2 is dissolved in DMC solvent and stirred thoroughly until completely dissolved to obtain a homogeneous and clear pretreatment solution. The concentration of LiPO2F2 in the pretreatment solution is 3wt%. The positive electrode prepared in step (1) is completely immersed in the pretreatment solution for 20 min. The electrode is microwaved at 1000 W for 10 min to obtain a microwave electrode, wherein the thickness of the positive electrode electrolyte interface film is 0.06 μm.
[0123] Examples 3-18 The difference between Examples 3-18 and Example 1 is that: The positive electrode electrolyte interface film is adjusted by adjusting the process parameters in step (2).
[0124] The relevant parameters of the battery cells prepared by Examples 1 to 18 are shown in Table 1.
[0125] Table 1
[0126] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: Step (2) is excluded; In step (5), VC, FEC and LiPF6 are dissolved in a compound solvent of EC, EMC and DMC in an argon atmosphere glove box to prepare a target electrolyte with a LiPF6 concentration of 1.2 mol / L, wherein the concentration of VC is 2 wt%, the concentration of FEC is 2 wt%, and the mass ratio of EC, EMC and DMC is 1:1:1.
[0127] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is as follows: Step (2) is excluded; In step (5), in an argon atmosphere glove box, LiPO2F2 and LiPF6 are dissolved in a compound solvent of EC, EMC and DMC to prepare a target electrolyte with a LiPF6 concentration of 1.2 mol / L, wherein the concentration of LiPO2F2 is 3 wt% and the mass ratio of EC, EMC and DMC is 1:1:1.
[0128] Test method: (1) Gas production test of chemical formation: In a constant temperature and humidity environment of 25℃ and relative humidity ≤40%, unformed packaged cells from the same batch (parallel samples ≥3) were selected, and their initial mass m0 was weighed using an electronic balance. The cells were sealed and fixed in a programmable formation cabinet and charged to 4.2V with a constant current of 0.05C to complete the formation process. After formation, the packaged cells were placed to room temperature, and the residual electrolyte on the surface of the packaged cells was wiped off. The mass m1 after formation was weighed using the same electronic balance. The mass difference Δm0 of the blank sample was subtracted, and the mass of gas produced by the formation of the cell was calculated by Δm=(m0-m1)-Δm0. Then, the mass was converted into the volume of gas produced by formation according to the ideal gas law to obtain the gas production of the cell.
[0129] (2) Liquid retention test: In a constant temperature and humidity environment of 25℃ and ≤40% relative humidity, the initial total mass m2 of the battery cell under test was weighed using an electronic balance. The battery cell was then slowly depressurized using a pressure relief fixture and completely disassembled in a cleanroom, separating the electrodes and diaphragm, and removing non-liquid-absorbing parts such as the outer shell, tabs, rubber stoppers, and aluminum-plastic film seals. The disassembled electrodes and diaphragm were placed in a clean weighing bottle and then placed in a vacuum drying oven at 80℃±2℃ and a vacuum degree ≤-0.095MPa for drying every 2 hours. Take out and weigh it quickly once in the test environment until the difference between two consecutive weighings is ≤0.2mg, which is considered constant weight. Record the total dry mass m3 of the electrode and the diaphragm; weigh the total mass m4 of the non-absorbent components; calculate the mass m5 of the remaining electrolyte using the formula: mass of remaining electrolyte = m2-m3-m4, and then combine it with the total mass m6 of the active material in the cell. Calculate the liquid retention of the cell using the formula: liquid retention = (m5 / m6)×100%. The cell to be tested is the cell prepared by step (7) of the above examples and comparative examples.
[0130] (3) Cyclic performance test: At a temperature of 25℃, the test cell was charged and discharged within the range of 3V to 4.3V at a rate of 0.5C, and the initial discharge capacity C1 was measured. After 250 cycles at the same rate and voltage range, the discharge capacity C2 of the 250th cycle was measured. After 500 cycles, the discharge capacity C3 of the 500th cycle was measured. The capacity retention rate of the cell after 250 cycles was calculated using the formula: Capacity retention rate = C2 / C1 × 100%, and the capacity retention rate of the cell after 500 cycles was calculated using the formula: Capacity retention rate = C3 / C1 × 100%.
[0131] The cells prepared by Examples 1-18 and Comparative Examples 1-2 were subjected to the above-mentioned formation gas production test, liquid retention test and cycle performance test. The test results are shown in Table 2.
[0132] Table 2
[0133] As can be seen from the test data in Table 2, this application places the formation process of the positive electrode electrolyte interface film before the cell assembly. Before the first charge and discharge of the cell, the positive electrode electrolyte interface film on the positive electrode sheet has already been formed. During the first charge and discharge of the cell, under the blocking effect of the positive electrode electrolyte interface film, an effective isolation is formed between the positive electrode active material and the electrolyte encapsulated inside the cell. The two no longer come into direct contact, reducing the film-forming reaction between the positive electrode active material and the electrolyte, thereby reducing the consumption of active components in the electrolyte during the film formation process of the positive electrode electrolyte interface film. This is beneficial to increasing the effective electrolyte content encapsulated inside the cell, compared with Comparative Example 1. Compared with Comparative Examples 1 and 2, the electrolyte retention of the cells prepared by Examples 1 to 18 of this application is increased by 4.4% to 23.1%, which helps to mitigate the concentration polarization effect of active ion transport during charge-discharge cycles and reduce the irreversible loss of active ions. Compared with Comparative Examples 1 and 2, the capacity retention rate of the cells prepared by Examples 1 to 18 of this application is increased by 0.4% to 2.6% after 250 cycles, and the capacity retention rate of the cells prepared by Examples 1 to 18 of this application is increased by 2.7% to 7.6% after 500 cycles. It can be seen that the embodiments of this application can effectively improve the electrochemical performance of the cells and extend the cycle life of the cells.
[0134] Furthermore, this application prepares a positive electrode electrolyte interface film on the positive electrode sheet before cell assembly, placing the film formation reaction of the positive electrode electrolyte interface film before the cell packaging process. This also allows the gas generated during the film formation process of the positive electrode electrolyte interface film to be completely discharged before cell packaging, avoiding the adverse effects of the gas generated during the film formation process on the cell. Compared with Comparative Examples 1 and 2, the cells prepared by Examples 1 to 18 of this application can reduce the amount of gas generated during cell formation by 9.4% to 71.7%, significantly reducing the residual gas inside the cell, reducing the risk of cell expansion, and thus improving the safety and production yield of the cell.
[0135] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0136] The foregoing has provided a detailed description of a method for preparing a battery cell, the battery cell itself, the battery, the vehicle, and the electrical device provided in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A method for preparing a battery cell, characterized in that, The preparation method includes: Before cell assembly, a positive electrode electrolyte interface film is prepared on the positive electrode sheet.
2. The preparation method according to claim 1, characterized in that, The step of preparing a positive electrode electrolyte interface film on the positive electrode sheet before cell assembly includes: Before cell assembly, the positive active material in the positive electrode sheet is immersed in a pretreatment solution to prepare a wetted electrode sheet. The pretreatment solution includes film-forming components of the positive electrode electrolyte interface film. The wetted electrode is subjected to microwave treatment to prepare a positive electrode electrolyte interface film on the surface of the positive electrode active material of the positive electrode.
3. The preparation method according to claim 2, characterized in that, The film-forming component includes at least one of vinylene carbonate, fluoroethylene carbonate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, vinyl sulfate, and lithium bis(oxalato)borate.
4. The preparation method according to claim 2 or 3, characterized in that, In the pretreatment solution, the concentration of the film-forming component is 0.1 wt% to 10 wt%.
5. The preparation method according to claim 4, characterized in that, In the pretreatment solution, the concentration of the film-forming component is 1wt%~5wt%.
6. The preparation method according to any one of claims 2 to 5, characterized in that, The step of immersing the positive active material in the positive electrode sheet in a pretreatment solution to prepare the wetted electrode sheet includes: The positive electrode active material in the positive electrode sheet is immersed in the pretreatment solution; When the positive electrode active material is immersed in the pretreatment solution for a first time, the positive electrode sheet wetted with the pretreatment solution is removed from the pretreatment solution and suspended in the air until the suspension time reaches a second time or no liquid drips from the surface of the positive electrode sheet within a third time, thus obtaining the wetted electrode sheet.
7. The preparation method according to claim 6, characterized in that, The first duration is 5 min to 30 min; and / or, the second duration is greater than or equal to 30 min; and / or, the third duration is 1 min to 5 min.
8. The preparation method according to any one of claims 2 to 7, characterized in that, The microwave treatment of the impregnated electrode is performed at a power of 100W to 1000W for a duration of 5min to 20min.
9. The preparation method according to any one of claims 2 to 8, characterized in that, The step of microwave treating the wetted electrode to prepare a positive electrode electrolyte interface film on the surface of the positive electrode active material of the positive electrode includes: The wetted electrode sheet is subjected to microwave treatment to obtain a microwave electrode sheet; The positive electrode active material in the microwave electrode sheet is immersed in the target solvent; When the positive electrode active material is immersed in the target solvent for a period of four time, the microwave electrode sheet immersed in the target solvent is removed from the target solvent and suspended in the air until the suspension time reaches a period of five time or no liquid drips from the surface of the microwave electrode sheet within a period of six time, thus obtaining a cleaned electrode sheet. The cleaned electrode is dried to obtain a positive electrode electrolyte interface film formed on the surface of the positive electrode active material of the positive electrode.
10. The preparation method according to claim 9, characterized in that, The fourth duration is 5 min to 30 min; and / or, the fifth duration is greater than or equal to 30 min; and / or, the sixth duration is 1 min to 5 min.
11. The preparation method according to any one of claims 1 to 10, characterized in that, The thickness of the positive electrode electrolyte interface film is 0.005 μm to 0.15 μm.
12. The preparation method according to any one of claims 1 to 11, characterized in that, The preparation method further includes: A dry cell is obtained by assembling a positive electrode sheet with a positive electrolyte interface film. The target electrolyte is injected into the dry cell to prepare the cell.
13. The preparation method according to claim 12, characterized in that, The target electrolyte includes a lithium salt, and the electrolyte also includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
14. A battery cell, characterized in that, The battery cell is prepared by the battery cell preparation method according to any one of claims 1 to 13.
15. A battery, characterized in that, The battery includes the cell as described in claim 14.
16. A vehicle, characterized in that, The vehicle includes a battery as described in claim 15 or a cell as described in claim 14, wherein the battery or the cell serves as a power source for the vehicle.
17. An electrical device, characterized in that, The electrical device includes the battery as described in claim 15 or the battery cell as described in claim 14, wherein the battery or the battery cell serves as the power supply for the electrical device.
